Study of prevalence of depression, anxiety and sexual dysfunction in females attending infertility clinic - Patel, Ripal; Suthar, Mahesh; Tadavi, Mehul; Vaidya, Yashasvi (International Journal of Research in Medical Sciences, 2025)
Background: Infertility is a significant social issue affecting individuals’ personal, social, and mental health. Infertility can be caused by infection in the man or woman but often has no apparent underlying cause. The most common cause is ovulatory problems, while male infertility is most commonly due to semen deficiencies. The experience of infertility and its treatments can be highly stressful, affecting work, family, and relationships. It can also affect sexual self-esteem, desire, and performance, leading to depression and social isolation. So, we conducted this study to determine the prevalence of depression, anxiety and sexual dysfunction in females attending infertility clinics from July 2022 to December 2022. Methods: This cross-sectional study included 100 females aged 18 to 45 years, who attended the infertility clinic at the obstetrics and gynaecology department of S.S.G. Hospital, Vadodara, from July to December 2022. Different diagnostic tools were used for depression, anxiety and sexual dysfunction, and the data were collected and analysed. Results: According to the study, 44% of infertile patients suffered from depression, while 58% experienced anxiety. Depression was more common among people aged 23 to 27 years who lived in rural areas and had a lower socioeconomic position. Anxiety was more common among people aged 28 to 32 who lived in rural areas, had a poor level of education, and were unemployed. Furthermore, 54% of patients reported sexual dysfunction, which was more common in joint households. Conclusions: This study concluded that the prevalence of depression and anxiety was 44%, and 58% in patients with infertility and sexual dysfunction was 54%.